Pension reform in Europe in the 90's and lessons for Latin America - Fox, Louise (ECLAC SantiagoCL, 2001)
Focuses on the lessons that Latin American countries may draw from the experience of Europe. Examines how reforms undertaken by the majority of countries of the region show different paths to be taken, as to how social security can be made economically sustainable.